Biblical poetry and the art of close reading - Couey, J. Blake; James, Elaine T. (Cambridge University Press, 2018)
This volume explores the aesthetic dimensions of biblical poetry, offering close readings of poems across the Hebrew Bible/Old Testament. Composed of essays by fifteen leading scholars of biblical poetry, it offers creative and insightful close readings of poems from across the canon of the Hebrew Bible/Old Testament (Psalms, wisdom poetry, Song of Songs, prophecy, and poetry in biblical narrative). The essays build on recent advances in our understanding of biblical poetry and engage a variety of theoretical perspectives and current trends in the study of literature. They demonstrate the rewards of careful attention to textual detail, and they provide models of the practice of close reading for students, scholars, and general readers. They also highlight the rich aesthetic value of the biblical poetic corpus and offer reflection on the nature of poetry itself as a meaningful and enduring form of art